Fuelling war or buying peace: The role of corruption in conflicts - Philippe LeBillon (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
Corruption is endogenous to many political structures and serves key functions beyond the self-interest of public officials and politicians. Like violence, corruption participates in political ordering and, although corruption may in itself play a corrosive role on economies and rule-based institutions, it forms part of the fabric of social relations. This endogenous character means that conflicts may arise more from changes in the pattern of corruption, than from corruption itself. Domestic or external shocks affecting this pattern may lead to open conflicts reducing corruption. Yet, in a context of dwindling public rents and weak institutions, conflicts can degenerate into even further illegitimate and predatory rule characterized by a shift from monopolistic forms of corruption to criminal and competitive ones. Such pattern of corruption frequently `fuels' violent conflicts. Controversially, a move towards peace might be `paying' for it by facilitating the emergence of a corrupt order. Acknowledging the negative long-term effects of such policy, the challenge of peace-building initiatives and reforms is therefore to progressively shift individual incentives from competition over immediate corrupt gains towards broadly rewarding relations of benevolence and justice. – conflict ; corruption ; structural change
Keywords: O17; O50; Z13; 330; Korruption; Welt; Politische Stabilität; Politischer Konflikt